Improvement of Tillering and Grain Yield by Application of Cytokinin Derivatives in Wheat and Barley - Radoslav Koprna; Jan F. Humplík; Zdeněk Špíšek; Magdaléna Bryksová; Marek Zatloukal; Václav Mik; Ondřej Novák; Jaroslav Nisler; Karel Doležal (Agronomy, 2020)
Three cytokinin derivatives (CKd) designated as RR-G, RR-O, and RR-V applied by foliar spraying at tillering, and one compound previously described as a cytokinin antagonist (CKa) designated as RR-P applied as a seed coating were tested in winter wheat and spring barley in field trial experiments. The aim of the study was to examine the influence of the compounds that were tested on the number of productive tillers, grain yield, and endogenous CK content. With the exception of the compound RR-V, the measured parameters clearly showed the stimulatory effects of CKd on tillering and grain yield in spring barley and winter wheat. The RR-V showed a stimulatory effect on the number of productive tillers and yield in spring barley, but not in winter wheat. Although in winter wheat CKa stimulated both the number of productive tillers and the grain yield, there was an inhibitory effect in terms of the number of productive tillers observed in spring barley. The results of the endogenous cytokinin analysis suggested, among others, the importance of the role of isopentenyl-adenine types of cytokinins in the tillering of spring barley. In conclusion, the cytokinin derivative compounds with an agonistic or antagonistic role showed strong potential for application in the future development of plant growth regulators.